The Nexus between Type of Energy Consumed, CO2 Emissions, and Carbon-Related Costs - Rokhmawati, Andewi (International Journal of Energy Economics and Policy, 2020)
Reducing carbon emissions while minimizing carbon costs is the main objective of Indonesian carbon management. Using data from 2016, this article focuses on 475 Indonesian manufacturing firms with consumption greater than 6,000 tons of oil equivalent mandated by regulation to reduce their emissions. This study examines the effect of the type of energy consumed on carbon-related costs, with CO2emissions as the mediating variable. The study decomposes the type of energy consumed, namely into coal, natural gas, diesel, and electricity. The results show that: 1) Coal, natural gas, diesel, have a positive effect on CO2emissions; electricity has a negative effect on CO2emissions; 2) electricity, and CO2emissions have a negative effect on costs; and 3) CO2emissions significantly mediated the effect of coal, natural gas, diesel, and electricity on costs. The findings imply that firms’ investment in an efficient machine and technology required to reduce CO2emissions, as mandated by the regulation, has seemingly been unable to reduce the CO2emissions produced by fossil fuels but has been able to reduce CO2emissions from consumed electricity. Moreover, such investment seems able to reduce carbon-related costs. Policymakers should review the Indonesian energy mix from fossil fuels and socialize to firms that using the source of power from electricity is cleaner and cheaper than fossil fuels so that firms may be considered to shift fossil fuels energy into electricity. Hence, the government should ensure the availability of electricity supply generated from cleaner energy sources. Keywords: CO2; Costs; Electricity; Energy Management; Fossil Fuels; Path Analysis JEL Classifications: Q4; Q51; L5 DOI: https://doi.org/10.32479/ijeep.9246